Cation‐Doped SrTaO2N Prepared through a Flux Method for Visible‐Light‐Driven Water Splitting. Issue 4 (13th January 2023) - Obata, Keisuke; Higashi, Tomohiro; Ye, Feifan; Katayama, Masao; Takanabe, Kazuhiro
Abstract: Semiconductor photocatalysts for water splitting is considered one of the most promising technologies for solar energy conversion. SrTaO2 N has a band gap of 2.1 eV and is a candidate for achieving visible‐light‐driven water splitting. However, its poor charge separation efficiency limits its water splitting efficiency, which can be attributed to the charge recombination induced by reduced Ta 4+ sites, which act as recombination centers. This study focuses on the improvement of photocatalytic activity of SrTaO2 N by introducing foreign metal cations with a low oxidation state to suppress the formation of reduced Ta 4+ sites. Among the investigated samples, 1.0 mol % Ga 3+ ‐doped SrTaO2 N was found to improve the photocatalytic activity significantly. X‐ray photoelectron spectroscopy (XPS) data show that the formation of Ta 4+ species is suppressed after Ga doping, which might be responsible for the photocatalytic activity improvement of SrTaO2 N. Abstract : Semiconductor photocatalysts : A facile method, namely doping of foreign metal cations with a low oxidation state, was investigated to improve the photocatalytic activity of SrTaO2 N. Among various cations, Ga 3+ was found to be the most effective dopant at the B‐site in the perovskite structure, which successfully suppresses the formation of recombination centers coming from Ta 4+ .